Kamisama kiss. Vol. 2 - Suzuki, Julietta (Kamisama Kiss, 2011)
When a hot teen idol transfers to the local school, Nanami does not want to miss her chance to meet him, so Tomoe reluctantly agrees to let her enroll in the school, but her role as a deity causes more problems than either expected.